The metabolic characteristics and environmental adaptations of the intertidal bacterium Palleronia sp. LCG004 - Wang, Zekai; Wang, Jiahua; Yu, Xi; Zhang, Hongcai; Liu, Jie; Cao, Junwei; Fang, Jiasong; Song, Zengfu; Zhang, Li (Frontiers in Microbiology, 2024)
The intertidal zone, a dynamic interface of marine, atmospheric, and terrestrial ecosystems, exposes microorganisms to rapid shifts in temperature, salinity, and oxidative stress. Strain LCG004, representing a novel Palleronia species, was isolated from the Lu Chao Harbor’s intertidal seawater in the Western Pacific Ocean. The genome of the organism reveals its metabolic versatility, enabling the utilization of various organic substrates—ranging from organic acids, amino acids, to sugars, and encompassing complex carbohydrates—as well as adept handling of inorganic nutrients, thereby highlighting its significant role in the cycling of nutrients. The strain is equipped with multiple osmoprotectant transporters, deoxyribodipyrimidine photo-lyase, and a comprehensive antioxidant defense system, featuring with multiple catalases, peroxidases, and superoxide dismutases, enabling it to withstand ever-changing environmental conditions, UV radiation, and oxidative challenges. Notably, LCG004 exhibited enhanced growth and cell aggregation under oligotrophic conditions, promoted by light exposure, underscoring the significant influence of light on its morphological and physiological attributes. This study elucidates strain LCG004’s metabolic characteristics and ecological potential, and offers insights into its contributions to biogeochemical cycles and survival strategies in one of nature’s most fluctuating environments.